Life-Forms and Biological Spectrum of Deeva Ka Daanda a Sacred Grove in Garhwal Himalaya - Ghildiyal, J. C.; Barthwal, Naveen; Khantwal, Ajay (Indian Forester, 2016)
Deeva Ka Daanda a sacred grove in Garhwal Himalaya, is a tradionally protected forest area with its rich plant diversity. It occupies an area in West Ameli Range in Garhwal Forest Division. The biological spectrum of this sacred grove reveals that the vegetation of this area is thero-phanerophytic. The life-forms observed were Phanerophytes (26.82%), Chamaephytes (5.79%), Hemicrytophytes (4.63%), Cryptophytes (7.45%), and Therophytes (34.1%).